The Europeanization of the Development Cooperation Policies: from Public Opinion to Public Policies - Victor Negrescu (CES Working Papers, 2011)
In the context of the growing importance of the cooperation for development in the European Union and the appearance of a common growing public opinion agreement supporting this kind of initiatives, it is necessary to understand if we can talk today about a true common European policy. Still covered on intergovernmental level and considered to be a part of the national foreign policies, EU development aid is still far from reaching the maximum of its efficiency. In this paper we try to introduce a new evaluation method of the cooperation for development policies and interpretation of the degree of Europeanization of the national policies, starting from the case studies of France, the Czech Republic and Romania, that will enable us to appreciate the stages that have to be completed by the member countries but also by the EU to realize a completely uniform European foreign assistance strategy. The understanding of the European development aid environment is also necessary for the elaboration and the implementation of the Romanian development cooperation policy which is just taking its first steps as an international donor.
Keywords: 330; Developing countries; development cooperation; Europeanization; public opinion; foreign aid Romania